A Textile RFID Antenna for Wearable Applications - Doan, Thi Ngoc Hien; Nguyen, Van Khang; Dao, Ngoc Chien (Old Journal, 2017)
In this paper, we present a configuration of a textile antenna for wearable applications of Radio Frequency Identification (RFID) technology. This antenna operates at a frequency of 2.45 GHz and it is implemented on a single layer dielectric. The dielectric used in this research is a Kevlar substrate having a dielectric constant of εr = 3.58 and a thickness of h = 0.254 mm. This material satisfies the requirements of flexibility of the wearable antenna. The radiating element designed in the form of text is the abbreviation of the Hanoi University of Science and Technology (HUST), HUST. The substrate has the dimension L= 45 mm and W = 16 mm. The radiation element is made of copper. This antenna is designed and simulated by using the commercial software CST Microwave Studio. The simulated reflection coefficient S11 is -18.26 dB and the gain of 2.2 dBi at the frequency of 2.45 GHz.